2022
DOI: 10.30643/jiksht.v17i1.163
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Dukungan Keluarga Dengan Self Management Pada Pasien DM Tipe 2

Abstract: Introduction: Diabetes mellitus type 2 is a common problem that occurs i people who have metabolic disorders characterized by increased blood sugar duet o decreased secretion by pancreatic beta cells or impaired insulin function. The relationship of family support with people with type 2 DM is closely related to the existence of support, individuals will feel cared for considered to be in the support of their families. Objectives: The purpose of this study was to determine the relationship between family suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Therefore, it can be inferred that there is no significant correlation between the level of education and the occurrence of hypoglycemia. This is supported by other research stating that there is no significant relationship between the level of education and an individual's ability to detect the occurrence of hypoglycemia [25]. This study also revealed that the group with the highest percentage experiencing symptomatic hypoglycemia is the unemployed group at 64.52%.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, it can be inferred that there is no significant correlation between the level of education and the occurrence of hypoglycemia. This is supported by other research stating that there is no significant relationship between the level of education and an individual's ability to detect the occurrence of hypoglycemia [25]. This study also revealed that the group with the highest percentage experiencing symptomatic hypoglycemia is the unemployed group at 64.52%.…”
Section: Discussionsupporting
confidence: 85%